THE EFFECTIVENESS OF MISTAKE BUSTER TECHNIQUE TO IMPROVE STUDENTS’ GRAMMAR MASTERY (An Experimental Research at Eight Grade of SMP Islam Pecangaan in the Academic Year 2017/2018) - Isma Fitriyani (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2018)
This research aims to determine the effectiveness of the mistake buster technique in improving students’ grammar mastery at eight grade students of SMP Islam Pecangaan. In this research, the writer used quantitative approach in the form true experimental design. The population of this research was eight grades of SMP Islam Pecangaan and the samples of this research were VIII A as experimental class and VIII B as control class of SMP Islam Pecangaan. In experimental class was taught by using Mistake Buster Technique while in control class was taught by using conventional technique. Random sampling was choosing as the technique of sampling. Then, the instrument of this research was test. The test was pre-test and post-test. This research consisted of five meetings with three treatments. The result of this research showed that the mean score of pre-test in experimental class was 61,61. After giving the treatment, it became 91,25. Then, the mean score of pre-test in control class was 55,62 and the post-test was 75,63. It showed that the score pre-test and post-test in experimental class was higher than control class. It means that the use of mistake buster technique was effective to increase students’ understanding about grammar. Besides that, the score of tobserve was 2,057 while the score of  ttable in 5% significance level was 2,009 . So, it showed the significant of tobserve > 5% = 2,057 > 2,009. It means that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. There was an effectiveness of mistake buster technique to improve students’ grammar mastery at eight grade students of SMP Islam Pecangaan.